Early growth, backfat thickness and body condition has major effect on early heifer pregnancy in Nellore cattle - Brunes, Ludmilla Costa; Baldi, Fernando S. [UNESP]; E Costa, Marcos F. Oliveira; Quintans, Graciela; Banchero, Georgett; Lôbo, Raysildo B.; Magnabosco, Claudio U. (FapUNIFESP (SciELO), 2022)
The aim was to evaluate the association between growth, carcass and visual scores traits with precocious calving in Nellore cattle. Birth weight (BW), weight at 120, 210, 365 and 450 days of age, pre and post-weaning average daily gain, rib eye area, backfat thickness (BF), rump fat thickness and visual scores obtained at 18 months were used for the analysis. Records from 700 females born between 2009 and 2015, exposed to mating starting at 11 months of age were analyzed. Discriminant analyzes were performed with the software Statistica. BW and BF showed the highest (P>0.01) discrimination value for early heifer pregnancy (EP). Extreme intrauterine growth retardation can result in slower growth, which reflects in the worst reproductive performance, confirmed by the variation in BW between precocious and conventional heifers. The results also demonstrate that the level of body fat affects begin of puberty. Bone structure, musculature, depth, tail insertion and rump scores presented the highest discrimination value for EP. These traits can be used as selection tools to improve sexual precocity in female Nellore cattle. The results obtained in this study would support farmers to guide the heifer management and decisions in order to enhance the EP.
Keywords: Age at first conception; Carcass evaluation; Multivariate analyzes; Weight per-formance; Zebu